Case Report: sintilimab-induced Stevens-Johnson Syndrome in a patient with advanced lung adenocarcinoma - Li, Xueqin; Li, Guanghui; Chen, Diangang; Su, Linxi; Wang, Ru-peng; Zhou, Yi (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors (ICIs) have been widely applicated in clinical therapy in recent years. Skin-related adverse reaction is one of the most common adverse events for ICIs. Stevens-Johnson syndrome (SJS) is one of the serious cutaneous reactions threatening the life. Here, we reported a case of 76-year-old male patient with poorly differentiated metastatic lung adenocarcinoma, after 9 weeks exposure of sintilimab (3 doses) combined with paclitaxel liposome after concurrent chemotherapy/ radiotherapy, experienced Stevens-Johnson syndrome involving limbs, trunk, lip and the oral mucosa. Biopsy of the skin tissue showed infiltration of CD4 and CD8 positive T lymphocytes. We also found PD-L1 expression in the glands and the basal layer of the skin. This finding is distinct from the previously reported expression of PD-L1 on the surface of epidermal keratinocytes in patients with SJS due to immunotherapy.